2017
DOI: 10.2527/tas2016.0010
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and other mineral concentrations in feed and sheep's blood in Kosovo

Abstract: The aim of this study was to assess the concentration of Se and other minerals in sheep and the supplied feed. Four macrominerals (Ca, P, Mg, and S), 7 microminerals (Se, Fe, Zn, Cu, Mn, Co, and Mo), and 2 toxic minerals (Cd and Pb) were analyzed in 69 feed and 292 sheep blood samples from 30 farms in different regions of Kosovo. The samples were analyzed using inductively coupled plasma mass spectrometry, and mineral concentrations in whole blood were measured to assess their status in animals. Concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…The results of the current study agree with findings from Ademi et al (2017), who reported no effect of supplementation on whole blood Zn concentrations in eastern Europe. Considerations should include Zn source bioavailability in mineral supplements, because organic sources of a mineral are generally identified as more bioavailable than inorganic sources (Rojas et al, 1995;Spears, 2003).…”
Section: Serum Znsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of the current study agree with findings from Ademi et al (2017), who reported no effect of supplementation on whole blood Zn concentrations in eastern Europe. Considerations should include Zn source bioavailability in mineral supplements, because organic sources of a mineral are generally identified as more bioavailable than inorganic sources (Rojas et al, 1995;Spears, 2003).…”
Section: Serum Znsupporting
confidence: 92%
“…Cooperative field studies help producers and scientists understand in-field management practices and responses, specifically, mineral supplementation strategies, trace mineral concentrations in feedstuffs, mineral deficiencies in the animal, and the effects of supplementation on animal status (Dargatz and Ross, 1996;Menzies et al, 2003;Ademi et al, 2017;Keady et al, 2017). Dietary mineral concentrations are often quantified but do not equate directly to animal status, so biological samples must be taken (Dargatz and Ross, 1996;Herdt and Hoff, 2011;Ademi et al, 2017). Serum trace mineral concentrations have their own set of limitations when evaluating status of an animal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total whole-blood Se in sheep has been reported to range between 0.02 and 0.36 mg/L (Ademi et al 2017). Qin et al (2007) and Cobanova-Boldizarova et al (2008), when supplementing with either Se-enriched LAB or yeast at 0.3 mg Se/kg DM in the diet, recorded concentrations of 0.3 mg/L in the whole blood.…”
Section: Intake Uptake and Excretion Of Sementioning
confidence: 98%